Metabolic responses to oral surgery under local anesthesia and sedation with intravenous midazolam: the effects of two different local anesthetics. - Meechan, J. G. (American Dental Society of Anesthesiology, 1992)
The effects of epinephrine-free and epinephrine-containing local anesthetic solutions on plasma potassium and blood glucose concentrations were investigated in 20 patients undergoing oral surgery with intravenous midazolam sedation. Ten patients were randomly assigned to receive 4.4 mL of 2% lidocaine with 1:80,000 epinephrine as a local anesthetic and 10 were given 4.4 mL of 3% prilocaine with 0.03 IU/mL felypressin. There were significant changes from baseline potassium and glucose concentrations both within and between treatments in the early postinjection period. The epinephrine-containing local anesthetic significantly reduced the plasma potassium concentration 10 min after injection, by 0.16 +/- 0.20 mmol/L (mean +/- SD), and increased the blood glucose concentration at 10, 20, and 30 min (by 0.46 +/- 0.37, 0.63 +/- 0.45, and 0.56 +/- 0.28 mmol/L, respectively). Conversely, plasma potassium increased and blood glucose decreased 10, 20, and 30 min following the administration of the epinephrine-free solution. At 30 min potassium was increased by 0.24 +/- 0.16 mmol/L, and glucose was decreased by 0.23 +/- 0.16 mmol/L. It is concluded that epinephrine-free and epinephrine-containing local anesthetics differ in their metabolic effects during oral surgery with midazolam sedation.